Gravity, Weight and Their Absence - Pletser, Vladimir (SpringerBriefs in Physics,, 2018)
The book introduces readers to the concept of weightlessness and microgravity, and presents several examples of microgravity research in fluid physics, the material sciences and human physiology. Further, it explains a range of basic physical concepts (inertia, reference frames, mass and weight, accelerations, gravitation and weightiness, free fall, trajectories, and platforms for microgravity research) in simple terms. The last section addresses the physiological effects of weightlessness. The book's simple didactic approach makes it easy to read: equations are kept to a minimum, while examples and applications are presented in the appendices. Simple sketches and photos from actual space missions illustrate the main content. This book allows readers to understand the space environment that astronauts experience on board space stations, and to more closely follow on-going and future space missions in Earth orbit and to Mars.